Influence of Groundwater Depth on Salt Migration and Maize Growth in the Typical Irrigation Area - Liping Dai; Qingfeng Miao; Haibin Shi; Zhuangzhuang Feng; Yuxin Li; Yong Liu; Yongli Xu; Rigan Xu; Weiying Feng (Agronomy)
Groundwater depth has a significant impact on salinization in irrigated areas. In this study, different groundwater depths were controlled via pit tests and we conducted pit tests with different groundwater depths (DGWs) to investigate the relationship between irrigation water volume and salt migration during the crop growth period, as well as the influence of DGW on maize growth and yield. The aim of this study was to determine an appropriate DGW for maize growth in the Hetao Irrigation District, the largest irrigation area of Asia, under the dual goals of water conservation and salt control. The results showed that the upward replenishment of groundwater was 179.60 mm, 139.17 mm, 119.98 mm, 68.62 mm, and 48.38 mm for each respective DGW, i.e., negatively correlated with DGW during the maize growth period. Soil electrical conductivity (EC) was exponentially related to DGW. For DGWs > 1.75 m, surface soil EC decreased significantly and soil EC exhibited less variation with DGW. Moreover, the desalination rate and depth after irrigation were improved at DGW values of 2.00 m and 2.25 m. Shallow DGW values resulted in increased evapotranspiration and intensified crop stress, which reduced water use efficiency. To reduce resource waste and salt stress on crops, we suggest that a DGW of 2.00~2.25 m is more suitable for maize growth and development. These results provide a reference for determining appropriate DGWs for maize growth in salinized irrigation areas.